Determinan Profitabilitas Bank Studi Empiris di Indonesia - Arifian, Dini; Noor, Juliansyah (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
This study aims to investigate the determinants that impact the profitability of 20 banks in Indonesia period from 2013 to 2021, as low profitability reduces banks' ability and willingness to finance the broader economy. The study uses panel data analysis, conducting three profitability bank measures: the net interest margin, the return on assets, and the return on equity. Inflation and gross domestic product growth were control variables that had not been studied in prior studies. The study's findings indicate that capital adequacy ratio, nonperforming loans, operation expenses, and bank size have strong effects on profitability. The study also finds that inflation and gross domestic product growth variables influence bank profitability. The study also finds that the direction of causality is not consistent among bank’s profitability measurements. According to our knowledge, this study is the first to investigate internal and external determinants of bank profitability in Indonesia that have not been studied previously. Keywords: bank’s profitability, bank size, capital adequacy ratio, nonperforming loans, operating expenses